Correlation between Educational Technology Literacy and Online Learning Anxiety of Junior High School Students - Akis, Dwi Ihza Sari; M. Miftach Fakhri; Pramudya Asoka Syukur; Fadhel Akbar; Devi Miftahul Jannah (Fakultas Teknik, Universitas Negeri Makassar, 2025)
Education is undergoing significant transformations as technology advances, particularly in the context of increasingly common online learning, fueled by the COVID-19 pandemic and the industrial revolution 4.0. This article investigates the relationship between educational technology literacy and junior high school students' anxiety during online learning. Respondents from SMPN 1 Kahu, a total of 66 students, completed a questionnaire assessing their technology use proficiency and anxiety levels. The results showed that students' technological literacy tended to be good (mean 3.4-4.2), with relatively low anxiety levels (mean 2.6-3.3). The correlation between technological literacy and anxiety varied; some students felt a positive influence, while others believed that technological literacy could reduce anxiety. The research method used a quantitative approach with survey method and random sampling technique. The findings provide insights into students' readiness for online learning and its implications for anxiety. This study strengthens the results of previous research, confirming that technological literacy can influence students' perception of anxiety during online learning.